2020
DOI: 10.1111/tid.13388
|View full text |Cite
|
Sign up to set email alerts
|

A case of successful treatment of severe COVID‐19 pneumonia with favipiravir and tocilizumab in post–kidney transplant recipient

Abstract: We report a case of COVID‐19 in kidney transplant patient in Thailand. A 58‐year‐old 2 years post–kidney transplant recipient, with maintenance immunosuppression of tacrolimus, mycophenolate mofetil (MMF), and prednisolone, presented with acute diarrhea which followed by fever on day 12. Symptoms of pneumonia together with lymphopenia from complete blood count were developed on day 7 after onset of fever with the x‐ray finding of bilateral multifocal patchy infiltration. COVID‐19 infection has been confirmed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 16 publications
0
26
0
Order By: Relevance
“…To be included, the study must have reported clinical data on adult (A-CA) or pediatric (P-CA) cancer patients and SOT or HCT recipients with confirmed COVID-19. Our inclusion and exclusion criteria identified 64 SOT studies, 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 11 HCT studies,…”
Section: Methodsmentioning
confidence: 99%
“…To be included, the study must have reported clinical data on adult (A-CA) or pediatric (P-CA) cancer patients and SOT or HCT recipients with confirmed COVID-19. Our inclusion and exclusion criteria identified 64 SOT studies, 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 11 HCT studies,…”
Section: Methodsmentioning
confidence: 99%
“…Given the paucity of patients identified within the selection criteria in each selected article, the results are reported as a narrative review. Data extracted from each study [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 …”
Section: Methodsmentioning
confidence: 99%
“…Antivirals should mainly be chosen with care, especially in recipients with long-term immunosuppressive therapy and with liver and renal dysfunction as it can affect the metabolism of drugs and leads to drug interactions (Xia and Wang 2020). Indeed, the interaction between antivirals (favipiravir) and tacrolimus was shown to cause reversible AKI (Thammathiwat et al 2020). Further, the simultaneous use of lopinavir/ritonavir (LPV/r) and HCQ as an antiviral regimen with tacrolimus in solid organ transplant recipients with COVID-19 is not recommended.…”
Section: Covid-19 Studies In Kidney Transplant Recipientsmentioning
confidence: 99%